Level of Effectiveness of Business Ethics for Running a Start Up: Basis for Crafting a Development Plan: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Business ethics is an essential aspect of any startup. It is a set of moral principles that guidethe behavior and actions of individuals in the organization. Effectiveness in business ethicsensures that the company makes decisions that align with its values, mission, and vision andcan improve employee morale and productivity while reducing legal risks.In our study, the composite weighted mean of the enterprise's core values was 4.32 for singlesand 4.28 for married people, which were both interpreted as strongly agreeing. For day-to-daydecisions, the weighted mean by single is 4.68 and married is 4.28, both interpreted stronglyagree, while the conflict of interest by single is 4.36 and married is 4.68, both interpretedstrongly agree, and the company involved in the community is 4, interpreted agree, andmarried is 4.64, interpreted strongly agree. In conclusion, the level of effectiveness ofbusiness ethics is critical for running a successful start-up.A development plan for a startup should include a strong emphasis on ethical behavior andpractices. This may include implementing a code of conduct or ethics policy, providing ethicstraining for employees, conducting regular audits to ensure compliance, and regularlyreviewing and updating policies and procedures to reflect changing ethical standards andpractices. By prioritizing ethics, a startup can build a strong foundation for long-term successand growth.
Keywords: Business